The effects of calf massage in boys with Duchenne muscular dystrophy: a prospective interventional study. Issue 26 (18th December 2021) - Carroll, Kate; Yiu, Eppie M.; Ryan, Monique M.; Kennedy, Rachel A.; de Valle, Katy
Abstract: Purpose: We explored the effects of standardized calf massage in ambulant boys with Duchenne muscular dystrophy (DMD) using a prospective study design. Materials and Methods: Twenty boys completed two study visits, 1 week apart. At both visits, each leg received a 10-min calf massage (intervention) and a 10-min control rest period (placebo) in randomized order. Muscle length of calf and hamstrings and gastrocnemius stiffness were measured by a blinded assessor before and after intervention and placebo. Measures of gait function (timed 10-m walk/run and spatio-temporal gait parameters); gastrocnemius muscle ultrasound findings; participant perception of leg pain, stiffness and effort of walking and general psychological well-being were also collected. Results: Consistent significant small increases in muscle length of soleus, gastrocnemius and hamstrings were recorded post-massage, and gastrocnemius stiffness decreased. Small changes in gastrocnemius and soleus length only were also recorded following the control rest period. Gait function and general well-being remained stable throughout. Measurement across both study visits suggested that gains in muscle length may be cumulative with repeated massage. Conclusions: Calf massage is safe and associated with benefits to muscle length and stiffness for ambulant boys with DMD. Implications for Rehabilitation: In a small sample of boys with Duchenne muscular dystrophy, calf massage was found to be safe, well-tolerated and associated with increased muscle length and decreased stiffness. The use of massage may assist in managing muscle length in boys with Duchenne muscular dystrophy.